The unfolded protein response and cellular stress / B The unfolded protein response and cellular stress / edited by P. Michael Conn - Conn, Patrick Michael (The unfolded protein response and cellular stress, 2011)
This volume provides descriptions of the occurrence of the UPR, methods used to assess it, pharmacological tools and other methodological approaches to analyze its impact on cellular regulation. The authors explain how these methods are able to provide important biological insights. This volume provides descriptions of the occurrence of the UPR, methods used to assess it, pharmacological tools and other methodological approaches to analyze its impact on cellular regulation. The authors explain how these methods are able to provide important biological insights